Lacticaseibacillus rhamnosus attenuates uremic toxins in patients with nondialysis chronic kidney disease through the anti-inflammatory molecules - Asada Leelahavanichkul; Pornpimol Phuengmaung; Thansita Bhunyakarnjanarat; Warerat Kaewduangduen; Pimmada Boonnaj; Pichanan Tengamnuay; Wiwat Chancharoenthana; Somkanya Tungsanga; Suwasin Udomkarnjananun; Somying Tumwasorn (Scientific Reports)
Abstract Because of the strain-dependent effect and the lack of simultaneous in vitro test with limited clinical data on Lacticaseibacillus rhamnosus L34 (L34) isolated from the Thai population, L34 was tested and compared with L. rhamnosus GG (LGG). The before and after test using L34 and a randomized placebo-controlled trial using placebo, L34, and LGG, for 4 weeks in patients with non-dialysis chronic kidney disease stage 3–5 (CKD) together with the in vitro experiments using indoxyl sulfate (IS, a representative uremic toxin) were performed. In comparison with the baseline, 4-week-L34 administration reduced gut-derived uremic toxins (GDUTs), except total IS, and attenuated several biomarkers, including i) systemic inflammation, as measured by cytokines and neutrophil extracellular traps using citrullinated histone 3, cell-free DNA, and fluorescent-stained nuclear morphology; ii) gut permeability defect (beta-d-glucan but not by endotoxemia); and iii) gut dysbiosis (fecal microbiome analysis). Additionally, L34-conditioned media attenuated IS-induced injuries on Caco-2 enterocytes, THP-1-derived-macrophages, and isolated neutrophils. Despite the possible different active compounds, both probiotics similarly attenuated IS-induced inflammation in vitro and in patients when compared with the placebo. In conclusion, L34 and LGG similarly attenuated systemic inflammation in patients with CKD, through the improved gut dysbiosis and anti-inflammation.